Attitudes, acceptance and hesitancy among the general population worldwide to receive the COVID-19 vaccines and their contributing factors: A systematic review - Fidelia Cascini; Ana Pantovic; Yazan Al-Ajlouni; Giovanna Failla; Walter Ricciardi (EClinicalMedicine, 2021)
Background: High rates of vaccination worldwide are required to establish a herd immunity and stop the current COVID-19 pandemic evolution. Vaccine hesitancy is a major barrier in achieving herd immunity across different populations. This study sought to conduct a systematic review of the current literature regarding attitudes and hesitancy to receiving COVID-19 vaccination worldwide. Methods: A systematic literature search of PubMed and Web of Science was performed on July 5th, 2021, using developed keywords. Inclusion criteria required the study to (1) be conducted in English; (2) investigate attitudes, hesitancy, and/or barriers to COVID-19 vaccine acceptability among a given population; (3) utilize validated measurement techniques; (4) have the full text paper available and be peer-reviewed prior to final publication. Findings: Following PRISMA guidelines, 209 studies were included. The Newcastle Ottawa (NOS) scale for cross-sectional studies was used to assess the quality of the studies.Overall, vaccine acceptance rates ranged considerably between countries and between different time points, with Arabian countries showing the highest hesitancy rates compared with other parts of the world. Interpretation: A variety of different factors contributed to increased hesitancy, including having negative perception of vaccine efficacy, safety, convenience, and price. Some of the consistent socio-demographic groups that were identified to be associated with increased hesitancy included: women, younger participants, and people who were less educated, had lower income, had no insurance, living in a rural area, and self-identified as a racial/ethnic minority.